2019
DOI: 10.1002/smj.3037
|View full text |Cite
|
Sign up to set email alerts
|

Managing history: How New Zealand's Gallagher Group used rhetorical narratives to reprioritize and modify imprinted strategic guideposts

Abstract: Research Summary Imprinting theory predicts that organizations are imprinted with multiple intersecting imprints that persist. Evidence suggests, however, that imprints are sometimes reprioritized or modified, implying that they can be strategically managed. We draw upon rhetorical history research and an in‐depth historical case study of New Zealand's Gallagher Group to describe how one firm managed its imprints. Our inductive theorizing links historically imprinted strategic guideposts to decision‐making via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 67 publications
3
65
0
1
Order By: Relevance
“…As a result, existing studies continue to see traditions as a restraint on managerial agency, rather than as an interpretive resource that can be used to promote change and adaptation while still honoring the past. One exception is Sinha et al (2020). Beyond observing rhetorical strategies of periodization or bracketing in a family business that strategically restructured its family history narratives to draw attention to some events in the family history and distract attention from others, the authors observed that the family business modified historical narratives beyond their original meaning—a process referred to as modifying guideposts .…”
Section: Rhetorical Historymentioning
confidence: 99%
“…As a result, existing studies continue to see traditions as a restraint on managerial agency, rather than as an interpretive resource that can be used to promote change and adaptation while still honoring the past. One exception is Sinha et al (2020). Beyond observing rhetorical strategies of periodization or bracketing in a family business that strategically restructured its family history narratives to draw attention to some events in the family history and distract attention from others, the authors observed that the family business modified historical narratives beyond their original meaning—a process referred to as modifying guideposts .…”
Section: Rhetorical Historymentioning
confidence: 99%
“…Because of the prominence of history in family businesses, these firms have often been stigmatized as a form of business organization that is steadfast to its history and traditions, path dependent, conservative, resistant to changes and unable to adapt to dynamic and constantly evolving markets (Chandler, 1977; Morck & Yeung, 2003; Poza et al, 1997). Yet, family businesses remain dominant in any economy (La Porta et al, 1999), many of them are highly innovative (De Massis et al, 2018), resilient to crises, and equipped with the stamina to pursue entrepreneurial projects over generations (Jaskiewicz et al, 2016; Sinha, Jaskiewicz, Gibb, & Combs, 2020). The latter is consistent with emerging research suggesting that the history and traditions of families and their businesses do not have to be a rigid burden but, in some cases, can be a holy grail for enduring innovation and change (Erdogan et al, 2020; Jaskiewicz, Combs, & Ketchen, 2016; Suddaby & Jaskiewicz, 2020).…”
Section: Special Issue Themementioning
confidence: 99%
“…While researchers thus recognize the paradoxical nature of the family business as an organization that can be burdened or empowered by history, theory on how history actually ties into family business’ tradition, change, and aspiration remains scarce (De Massis, Frattini, Kotlar, Messeni Petruzzelli, & Wright, 2016; Erdogan et al, 2020; Sinha et al, 2020; Suddaby, Coraiola, Harvey, & Foster, 2020; Suddaby & Jaskiewicz, 2020). One reason for this unsatisfactory status quo is the weak connection between history and family business scholarship that has limited current understanding of what family business scholars can learn from the wealth of history and historical research, and how they can integrate related learnings in the study of family business (e.g., Colli, 2003; Colli & Fernandez Perez, 2020).…”
Section: Special Issue Themementioning
confidence: 99%
See 1 more Smart Citation
“…The use of (historical) narratives to investigate how business leaders "promote conceptions of identity likely to resonate with audiences" (Basque & Langley, 2018, p. 4) is well established in organizational identity research (Zundel et al, 2016;Anteby & Molnár, 2012); and recently also emerged in family business research (e.g. Sinha et al, 2019). We follow this tradition of rhetorical analysis and apply it to business ethics (see Werner, 2008).…”
Section: Data Sourcesmentioning
confidence: 99%